Analysis of Essential Elements for Plants Growth Using Instrumental Neutron Activation Analysis - R. L. Njinga; M. N. Moyo; S. Y. Abdulmaliq (International Journal of Agronomy)
In this study, a total of ten essential elements for plants growth in the Guinea savanna region of Niger State in Northern Nigeria have been identified in the soils using instrumental neutron activation analysis. The experimental results show good agreement with certified or literature values within the agreed percentage range of ±2.35% to ±8.69%. However, the concentration distributions of the ten identified elements in the soil samples within the studied area for plants growth revealed the following: Fe (123.4 ppm), Mn (2100.7 ppm), K (5544.3 ppm), Al (54752.4 ppm), Ti (3082.9 ppm), Ca (4635 ppm), V (54.3 ppm), Na (857.5 ppm), Mg (13924.1 ppm), and Dy (12.1 ppm). A further analysis of the two fundamental soil physical parameters for healthy growth of some common crops like egusimelon, groundnut, rice, yams, soybeans, cassava, and potato analyzed in this work revealed a pH range of 4.0 pH–8.0 pH and a temperature range of 28.0°C to 29.3°C, which are optimal for plant nutrients availability in the soils within the study area.